Heart within Brain - Varadharaj, Devi; Thirunavukarasu, Suresh; Purushothaman, Karthikeyan; Antonisamy, Vincent J; Balavenkata, Ramanan B (Journal of the Association of Physicians of India, 2023)
: Varadharaj D, Thirunavukarasu S, Purushothaman K, Heart within Brain. J Assoc Physicians India 2023;71(10):100-100.